SEGMENTASI WILAYAH BERDASARKAN KETERSEDIAAN FASILITAS PUBLIK (STUDI KASUS: KABUPATEN/KOTA DI PROVINSI NUSA TENGGARA TIMUR) - Anne Mudya Yolanda; Agung Satrio Wicaksono (NIAGARA Scientific Journal, 2022)
The availability of public facilities could be an indicator of regional development. The purpose of this study was to describe the segmentation of the availability of public facilities in Nusa Tenggara Timur province by regency/city. The K-Means Clustering analysis was used to divide the regencies/cities in Nusa Tenggara Timur province into three groups. The variables used in this K-Means Clustering analysis based on Nusa Tenggara Timur Village Potential Statistics are Public Spaces, Integrated Health Counseling Post, The Source of Main Street Illumination, Availability of Public Transportation, and Availability of Communication Facility. According to the findings and discussions, the first, second, and third clusters of the availability of public facilities byregencies/cities in Nusa Tenggara Timur Province consist of 8, 5, and 9 regencies/cities, respectively. Percentage of variability for this data is about 61.4 %. The segments with the lowest availability of public facilities are Sumba Barat regency, Belu regency, Sumba Tengah regency, Sabu Raijua regency, and Kupang City. The medium segment consists of Sumba Timur regency, Alor regency, Sikka regency, Ngada regency, Rote Ndao regency, Sumba Barat Daya regency, Nagekeo regency, and Malacca regency. The areas with the highest availability of facilities are Kupang regency, Timor Tengah Selatan regency, Timor Tengah Utara Regency, Lembata regency, Flores Timur regency, Ende regency, Manggarai regency, Manggarai Barat regency, and Manggarai Timur regency.